2012
DOI: 10.1029/2012jd017578
|View full text |Cite
|
Sign up to set email alerts
|

Response and sensitivity of the nocturnal boundary layer over land to added longwave radiative forcing

Abstract: [1] One of the most significant signals in the thermometer-observed temperature record since 1900 is the decrease in the diurnal temperature range over land, largely due to rising of the minimum temperatures. Generally, climate models have not well replicated this change in diurnal temperature range. Thus, the cause for night-time warming in the observed temperatures has been attributed to a variety of external causes. We take an alternative approach to examine the role that the internal dynamics of the stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 129 publications
(288 reference statements)
6
70
0
Order By: Relevance
“…This is much larger than the expected (small) LSAT diurnal cycle associated with zero solar heating in January ( Figure 1a) and hence is driven primarily by horizontal temperature advection. All the data uncertainties discussed in past studies [Karl et al, 1993;Easterling et al, 1997;Le Treut et al, 2007;Pielke et al, 2007aPielke et al, , 2007bFall et al, 2011;McNider et al, 2012] are much smaller than the magnitudes in Figure 1a and hence do not significantly affect the above results. Such large January MDTR values were not discussed in the past, probably because most previous studies focused on the anomalies and trends of MDTR (rather than the actual values of MDTR).…”
Section: 1002/2014jd021602mentioning
confidence: 52%
See 1 more Smart Citation
“…This is much larger than the expected (small) LSAT diurnal cycle associated with zero solar heating in January ( Figure 1a) and hence is driven primarily by horizontal temperature advection. All the data uncertainties discussed in past studies [Karl et al, 1993;Easterling et al, 1997;Le Treut et al, 2007;Pielke et al, 2007aPielke et al, , 2007bFall et al, 2011;McNider et al, 2012] are much smaller than the magnitudes in Figure 1a and hence do not significantly affect the above results. Such large January MDTR values were not discussed in the past, probably because most previous studies focused on the anomalies and trends of MDTR (rather than the actual values of MDTR).…”
Section: 1002/2014jd021602mentioning
confidence: 52%
“…Betts [2006] found that DTR is closely related to the surface net longwave radiation. The use of Tn as a diagnostic global warming metric was also cautioned because it is more sensitive (than Tx) to a variety of factors (e.g., land use change, station siting, and movement of station sites) [Pielke et al, 2007a[Pielke et al, , 2007bFall et al, 2011] and because it reflects a redistribution of heat by changes in atmospheric turbulence rather than by an accumulation of heat in the atmospheric boundary layer [McNider et al, 2012]. These points were clearly illustrated by the widespread timing of daily Tx and Tn occurrences [Wang and Zeng, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The seasonality shown in the daytime lapse rate was clearer than in the nighttime lapse rate (Figs. 3 and 4), suggesting that strong turbulent mixing controlled the daytime mixing layer but as expected, there was stabilized surface air (weak turbulence) in the nocturnal boundary layer (Stone and Carlson, 1979;Stull, 1988;Karl et al, 2006;McNider et al, 2012). Thus, the nighttime lapse rate clearly consistently varied much more than the daytime lapse rate over 1997 to 2013 (Figs.…”
Section: Surface Lapse Rate Trends and Seasonalitymentioning
confidence: 62%
“…Daytime and nighttime lapse rate trends demonstrate different properties largely due to the diurnal solar cycle, wind speed and its interaction with the land surface (Pepin, 2001;Karl et al, 2006;Mahrt, 2006;McNider et al, 2012). Wind strongly influences turbulent mixing and surface boundary layer depth (Stull, 1988;Pepin, 2001).…”
Section: Wind Influences On Lapse Rate Trendsmentioning
confidence: 99%
“…The ABL also plays an important role in the re-analysis (e.g., Tastula et al 2013) and understanding of polar climates (e.g., Atlaskin and Vihma 2012;Sterk et al 2013), as well as the so-called Arctic amplification (e.g., Esau et al 2012). In addition, McNider et al (2012) study the stable boundary layer over land and show that this coupled system can be very sensitive to changes in greenhouse gas forcing, surface roughness, heat capacity, and wind speed. …”
mentioning
confidence: 99%